Successful Delivery of Twin Pregnancy in Class U3b/C2/V1 Uterus by Bilateral Caesarean Section after Spontaneous Conception - Yasmine El-Masry; Ahmed M. E. Ossman; Mohammed El-Namoury; Sameh Sarsik (Hindawi Limited, 2015)
A case of a 19-year-old female with class U3b/C2/V1 uterus conceived a twin pregnancy with a fetus in each horn after spontaneous conception. She referred to our department with presentation of premature rupture of membranes, with a history of cesarean delivery of a single full term living fetus a year and a half before this delivery. Examination revealed two completely separate uterine horns with a fetus in each horn, two distinct externally rounded cervices, and a single vagina with a short nonobstructing vaginal septum in the upper part of the vagina. And as the appropriate mode of delivery is still unclear, each case should be managed as the condition requires, and in our case urgent bilateral caesarean sections were performed.